Pengaruh Tingkat Kematangan dan Lama Penyimpanan Terhadap Karakteristik Mutu Fisik Buah Lemon Lokal (Citrus X Limon) pada Kondisi Penyimpanan Ruang - Naibaho, Benika; Simanungkalit, Ferlando Jubelito; Nadapdap, Eppy Yerni (Universitas Batanghari Jambi, 2025)
This study aims to study the effect of the level of ripeness of local lemons (Citrus x limon) and storage time on the physical quality characteristics of local lemons under room storage conditions. Room storage conditions are intended to simulate the storage conditions of local lemons in local farmers and traditional markets in Medan City. Where farmers and traders store local lemons in baskets stored at room temperature, without using a refrigerator. This study was conducted experimentally using a completely randomized factorial design. The first factor is the level of ripeness: green (H), green-yellow (HK) and yellow (K). The second factor is the storage time (days): 0, 2, 4, 6, 8, 10 and 12 days. The parameters analyzed consisted of: weight loss, size loss and hardness. The results showed that the level of ripeness of local lemons (Citrus x limon) had a significantly different effect on weight loss ranging from 8.9388% - 10.6499%, fruit size loss (longitudinal) 3.16 mm - 4.94 mm and hardness 4.65 - 5.53 kg / cm2. The storage period of local lemons (Citrus x limon) had a significantly different effect on weight loss ranging from 0.0000% - 17.0168%; fruit size loss (longitudinal) 0.00 mm -7.19 mm; fruit size loss (transverse) 0.00 mm - 4.08 mm. The interaction between the level of ripeness and storage period of local lemons (Citrus x limon) had a significantly different effect on fruit hardness.